2007
DOI: 10.1007/s00103-007-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Inanspruchnahme medizinischer Leistungen

Abstract: The use of operations, visits to doctors and early diagnostic tests for children are examples of different services selected from the whole spectrum of preventative and therapeutic health service provisions in childhood and adolescence. In the German Health Interview and Examination Survey for Children and Adolescents (KiGGS), which is representative for Germany, 17,641 children and adolescents aged 0-17 or their parents were questioned on subjects such as their use of medical services. The use made of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
23

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 19 publications
2
31
0
23
Order By: Relevance
“…Again, kindergarten visit seems to have a positive influence on the timely and adequate identification and treatment of complaints like visual or hearing acuity and kinetic or cognitive development. Generally, our study results on IPERE and IIU by children from the included districts in NRW are in line with previous findings from the national KiGGS study [5,11] and with outcomes of the analyses of Koller and Mielck on school district level [6]. The prevalence rate of IPERE in children with migratory background in the current study was comparable with the prevalence rate observed in the KiGGS study for children with parents having both a migratory background [14].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Again, kindergarten visit seems to have a positive influence on the timely and adequate identification and treatment of complaints like visual or hearing acuity and kinetic or cognitive development. Generally, our study results on IPERE and IIU by children from the included districts in NRW are in line with previous findings from the national KiGGS study [5,11] and with outcomes of the analyses of Koller and Mielck on school district level [6]. The prevalence rate of IPERE in children with migratory background in the current study was comparable with the prevalence rate observed in the KiGGS study for children with parents having both a migratory background [14].…”
Section: Discussionsupporting
confidence: 91%
“…Although it may be assumed that public social security systems, as they exist in Germany, ensure universal access to health care services, inequalities have been described in countries with well-developed social security systems [1,5,8,10,11,18,19]. For example, the participation rate in regular health check-up examinations during childhood which are nationally recommended in Germany and covered by the health insurance has shown to be up to 20 % lower in families with a low socio-economic status compared to families with a high socio-economic status [5,10]. On the other hand, the immunisation status of children was less likely to be complete in families with a high socio-economic status [10,11,19], which might be attributed to increased scepticism about the usefulness of vaccinations in this population sub-group [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Das ging aus einem Vergleich mit der KiGGS-Studienpopulation (Basiserhebung) als auch der Bevölke-rungsstruktur der Stadt Leipzig hervor [24,25]. Die Inanspruchnahme der LIFE-Child-Studienpopulation lag im gesamten Verlauf über der KiGGS-Kurve [8]. Obwohl die untere Sozialschicht in der LIFE-Child-Population unterrepräsentiert war, reichte ihr Einfluss, um die Inanspruchnahme der anderen Sozialschichten insgesamt zu reduzieren.…”
Section: Introductionunclassified